THE IMPLEMENTATION ON POLICY PRACTICE OF CHINESE DIPLOMACY THROUGH CONFUCIUS INSTITUTE (CI) IN THAILAND - Muhammad Habib Rosyidi; Ario Bimo Utomo (POLITICO, 2022)
This paper will discuss the Implementation on Policy practice of Chinese diplomacy to Thailand through the establishment of the Confucius Institute (CI) and the significance for China-Thailand relations. The impact of the migration of Chinese people in the past has had an impact on the cultural closeness between the Chinese and Thai people. China's economic development and the close trade relations with Thailand have influenced the significance of Mandarin for Thai people. The Chinese government then responded to the need for Chinese language skills. This research is descriptive qualitative with secondary data. At the end of this paper, the author concludes that CI has played an active role as a manifestation of China's cultural diplomacy in Thailand through its cultural programs which indicate a good two-way communication between China and Thailand. In addition, the presence of CI in Thailand allows for public understanding of the diversity and hybridity of other individuals in Thailand.